Consumer Perceptions of Buying Behavior of Organic Vegetables with Planned Behavior Theory Approach - Kukuh Swan Sri Sabakti; Ratya Anindita; Riyanti Isaskar (HABITAT, 2022)
Organic vegetables are gaining popularity all over the world, and the number of consumers of organic vegetables is increasing. Developing countries like Indonesia, are still very minimal in consuming organic vegetables. Therefore, this study aims to identify the factors that drive buying behavior of organic vegetables. The research location was conducted in Malang Raya which was selected by purposive sampling and involved 128 respondents who became the research sample. The analytical method uses descriptive analysis and Structural Equation Modeling (SEM) is used to measure the effect of perceptions, preferences, attitudes, subjective norms and control of consumer behavior on purchase intentions and behavior. The results of the analysis show that the behavior of buying organic vegetables is largely determined by preferences and behavioral control through intention and there is a preference role that successfully mediates the relationship between consumer perceptions and intentions. Perceptions, attitudes and subjective norms cannot influence consumer intentions because most consumers and their environment do not have good knowledge so that consumer buying behavior of organic vegetables tends to be based on the control of the dangers. Market players and the government must cooperate with farmers and provide information and promotions regarding the advantages of organic vegetables which are expected to increase actual buying behavior of organic vegetables.